PERBEDAAN PERILAKU PENJAMAH MAKANAN SEBELUM DAN SESUDAH MENDAPATKAN PENYULUHAN HIGIENE SANITASI MAKANAN PADA WARUNG MAKAN DI TERMINAL TERBOYO SEMARANG - Meidia Atika Sari; Sulistiyani Sulistyani; Niki Astorina Yunita Dewanti (Jurnal Kesehatan Masyarakat (Undip), 2016)
Behaviour improvement was required by food handlers to overcome failure hygiene and food sanitation that produce eligible quality of food consumed by the public. Improved knowledge, attitude and practice is required by food handlers to improve hygiene and sanitation of food. Based on preliminary studies of laboratory test results obtained from six samples of food, there are 4 positive food samples E. coli, so that shows the quality of food at the food stalls in Terminal Teboyo not eligible. The purpose of this study was to analyze the differences in the behavior of food handlers before and after getting counseling hygiene and sanitation of food at the food stalls at Terminal Terboyo Semarang. The method of this research was a Quasi Experiment, with pretest and posttest research design. Sampling was done by total sampling as 35 peoples. The research data were taken using a questionnaire and observation sheet. The statistical test used is non parametric test - McNemar, at the 95% confidence level and borderline significance p <0,05. The results showed that the food handler knowledge’s before counseling were unfavorable 20 (57%) and after counseling were favorable 29 (82,9%), where as food handler attitude’s before counseling were unfavorable 19 (54,3%) and after counseling were favorable 28 (80,0%), then practice before counseling were unfavorable 21 (60.0%) and after counseling were favorable 19 (54,3%). A total of 35 food samples are 23 (65.7%) positive E. coli. There is a difference of knowledge (p = 0.001) and attitude (p = 0.004) before and after counseling, there is no difference before and after the practice of education (p = 0.500). There is no correlation between knowledge (p = 0.151) and attitude (p = 0.670) with the presence of E. coli, there is a connection with the practice of the presence of E. coli (p = 0.03). There is no difference in behavior (practice) before and after counseling. The need for ongoing counseling and oversight of all food vendors in Terminal Terboyo.